Marketing to baby boomer women - Brown, Mary (Henry Stewart Talks, 2010)
Why you should care, Busting the stereotypes, Boomer woman consumer influence model, Generational/ age cohort definition, Filtering values through cohort differences, The boomer age wave, Understanding her lifestage, Understanding affluence, Understanding gender influences, Understanding the mature mind, Key boomer women trends and insights for marketers